Myopericarditis secondary to silent autoimmune thyroiditis: a case of severe thyrotoxicosis - Pavel Antonio Montes Hernández; Dylani Rosa Ávila Salcedo; Jorge Alejandro Ayala San Pedro (European Journal of Case Reports in Internal Medicine, 2025)
Introduction: Myopericarditis is an uncommon but potentially severe complication of thyroid dysfunction. Although cardiovascular manifestations of hyperthyroidism are well documented, its association with myocardial and pericardial inflammation is rare and diagnostically challenging. Case Presentation: A 36-year-old previously healthy male presented with precordial chest pain and a 1-month history of diarrhoea, heat intolerance, palpitations, and unintentional weight loss. Laboratory evaluation revealed elevated cardiac biomarkers, and electrocardiogram showed diffuse ST-segment elevation suggestive of acute pericarditis. Coronary angiography demonstrated no obstructive coronary lesions. Thyroid function tests revealed suppressed TSH and markedly elevated free T4, with positive anti-thyroglobulin antibodies. Thyroid scintigraphy confirmed decreased uptake consistent with thyroiditis. A diagnosis of myopericarditis secondary to silent autoimmune thyroiditis was established. The patient was treated with nonsteroidal anti-inflammatory drugs, colchicine, beta-blockers, and methimazole, achieving complete clinical and biochemical recovery. Conclusion: This case emphasizes the importance of considering thyroid dysfunction in patients presenting with myopericarditis. Early recognition and targeted management can reverse myocardial injury and optimize patient outcomes.